59.2k views
17 votes
Solve the system by substitution.

y=4x-9
y=x-3

2 Answers

7 votes
X-3=4x-9
X=4x-9+3
X=4x-6
X+6=4x |-x
6=3x |:3
X=2
User Dennis Hunziker
by
4.8k points
5 votes

Answer:

(2, -1)

Explanation:

Given

  • y = 4x - 9
  • y = x - 3

Solving

  • Substitute the value of one of the y values from the other equation
  • 4x - 9 = x - 3
  • 3x = 6
  • x = 2
  • y = 2 - 3
  • y = -1
  • (2, -1)
User Treehouse
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.